Development of semi-conductive carbon nanotubes (CNTs) thin-film transistors into biosensors. - Zhong, Kang Tai. (2012)
It is notable that carbon nanotubes (CNTs) are of great interest to scientists in various fields of research for their uncanny ability to possess high thermal conductivity, therefore maintaining their structure when exposed to high temperature without taking any form of physical damage, as well as their unique mechanic properties that can withstand harsh biological conditions, which suggest great potential to be used in numerous bio applications.